Comorbidity of Major Depressive Disorder, Alcohol Use Disorder, and Anorexia Nervosa: A Rare Case Report - Ya-Lin Huang; Pei-Hsin Kao; Chien-Ho Lin (Taiwanese Journal of Psychiatry)
Background: Comorbidity is the co-occurrence of multiple disorders. Psychiatric patients often manifest themselves complicated cognitive and behavioral impairments as well as poorer outcomes. We intended to present a recently treated patient to show the challenging clinical complexities. Case Report: The patient was a 51-year-old woman patient, who presented herself with severe physical, psychiatric, and marital problems, including obvious malnutrition with purging and anorexic behavior, various depressive symptoms, as well as marital conflicts. Through our understanding and treatment in both inpatient and outpatient care, the patient had gradually resolved all her problems stepwise. Conclusion: This case report underscored complexity of comorbid major depressive disorder, alcohol use disorder, and anorexia nervosa, binge-eating/purging type as well as formulating all three conditions in the treatment. A transdiagnostic approach, such as the unified protocol, effectively addresses core emotional issues, while pharmacological interventions and integrated treatment strategies are crucial for symptom management and long-term recovery.